Resistance Exercise Enhances Cognitive Function in Mouse - Suijo, K.; Inoue, S.; Ohya, Y.; Odagiri, Y.; Takamiya, T.; Ishibashi, H.; Itoh, M.; Fujieda, Y.; Shimomitsu, T. (International Journal of Sports Medicine, 2013)
Physical exercise has been shown to increase adult neurogenesis in the hippocampus and to enhance synaptic plasticity. It has been demonstrated that these neuroprotective effects can be observed following aerobic exercise. However, it remains unknown whether plasticity molecules, such as brain-derived neurotrophic factor (BDNF) and cyclic AMP response element-binding protein (CREB), are expressed in the hippocampus following resistance exercise. We applied voluntary progressive-resistance wheel exercise (RE) for 14 days, and measured BDNF and CREB in the hippocampus. The Morris water maze was also performed to estimate learning and memory. Furthermore, we measured RE effects on mammalian target of rapamycin (mTOR) and 70-kDa ribosomal protein S6 kinase (p70S6K) mediating muscle protein synthesis in the soleus. As a result, we found that RE enhanced cognition and elevated BDNF and CREB expressions in the hippocampus. Also, RE activated the mTOR-p70S6K signaling pathway in the soleus. We found that phosphorylated mTOR and p70S6K were significantly positively correlated with BDNF expression. Our results indicated that resistance exercise drove the protein synthesis signaling pathway in the soleus and enhanced hippocampal synaptic plasticity-related molecules. These results suggest the beneficial effects of resistance exercise on cognitive function.
Keywords: resistance exercise; cognition; brain-derived neurotrophic factor; cyclic AMP response element-binding protein; mammalian target of rapamycin; 70-kDa ribosomal protein S6 kinase